Formulation and antifungal activity test of ethanol extract of cashew leaves (anacardium occidentale l.) gel for thrush against candida albicans fungus - Nurfantri Dinar; Himaniarwati; Wa Ode Ida Fitriah (Journal of Health Management and Pharmacy Exploration, 2026)
Cashew leaves (Anacardium occidentale L.) contain bioactive compounds, including flavonoids, saponins, and tannins, which exhibit potential antifungal activity against Candida albicans. This study aimed to formulate a canker sore gel containing ethanol extract of cashew leaves and to evaluate its antifungal activity against Candida albicans. The extract was obtained by maceration using 96% ethanol. Gel formulations were prepared at concentrations of 5%, 7.5%, and 10%. Physical evaluations included organoleptic properties, homogeneity, viscosity, pH, spreadability, and adhesiveness. Antifungal activity was assessed using the agar well diffusion method, with 2.2% nystatin as the positive control and the gel base as the negative control. All formulations met the requirements for a good gel preparation, exhibiting a semi-solid consistency, brownish-green color, characteristic odor, and homogeneous texture. The viscosity ranged from 120–250 dPas, and the pH was 6, indicating suitability for oral mucosal application. Inhibition zones against Candida albicans were 10.3 mm, 11.6 mm, and 12.3 mm for the 5%, 7.5%, and 10% formulations, respectively. The 7.5% and 10% formulations demonstrated strong antifungal activity. Statistical analysis revealed that concentration variation significantly affected antifungal activity (p < 0.05). Significant differences were observed between the 5% formulation and the 7.5% and 10% formulations, whereas no significant difference was found between the 7.5% and 10% formulations. Cashew leaf ethanol extract can be formulated into an effective canker sore gel, with the optimal antifungal activity observed at concentrations of 7.5%–10%.